Analysis of COVID-19 Impact on Micro, Small, and Medium Enterprises (MSMEs) Credit Distribution in East Java Banks - Evita Hayatun Nufus; Idah Zuhroh; Muhammad Sri Wahyudi Suliswanto (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: The purpose of this study was to determine the credit distribution level used as working capital assistance for Micro, Small, and Medium Enterprises (MSMEs) during the COVID-19 pandemic.Design/Methodology/Approach: This study used a sample of 8 cities/regencies in East Java. Meanwhile, the Micro, Small, and Medium Enterprises (MSMEs) credit recipients were the population of the sample areas. This research's analysis model was panel data regression (generalized least square) by considering the emergence of heteroscedasticity in cross-section data between regional objects. The control variables outside the COVID-19 were the BI rate, third-party funds (TPF), and inflation.Research findings: This study’s results showed that the COVID-19 pandemic had a significant negative impact only on medium-sized business loans, while micro and small business loans are more resilient. Besides, Micro, Small, and Medium Enterprises (MSMEs) credit was significantly positively influenced by TPF; inflation did not affect credit; the BI rate only negatively affected medium-sized business credit.Theoretical contribution/Originality: Studies on Micro, Small, and Medium Enterprises (MSMEs) credit-related to economic phenomena and monetary policy have been widely carried out. However, the catastrophic virus that causes long-term economic uncertainty and impacts banks and Micro, Small, and Medium Enterprises (MSMEs) still requires in-depth study. Also, this study employed the GLS model that considers heteroscedasticity, which is still rarely used in previous studies.Practitioner/Policy implication: This research can be essential information for the Indonesian Financial Services Authority (Otoritas Jasa Keuangan or OJK) and Bank Indonesia (BI) in policymaking, both regulatory aspects and bank liquidity provision, in stimulating Micro, Small, and Medium Enterprises (MSMEs) credit, especially in the COVID-19 pandemic era.Research limitation/implication: The impact of COVID-19 on Micro, Small, and Medium Enterprises (MSMEs) loans is still classified based on micro, small and medium. It is still not grouped based on the Micro, Small, and Medium Enterprises (MSMEs) business sector in various cities and regencies in East Java. The analysis has not been clustered based on the spatial concentration of the Micro, Small, and Medium Enterprises (MSMEs) recipient areas.